2015
DOI: 10.1016/j.bcp.2015.08.109
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 signaling: A common pathway for interactions between prooxidants and extracellular disulfide high mobility group box 1 (HMGB1) protein-coupled activation

Abstract: Necrotic cells passively release HMGB1, which can stimulate TLR4 in an autocrine fashion to potentially initiate “sterile” inflammation that maintains different disease states. We have shown that prooxidants can induce NF-κB activation through TLR4 stimulation. We examined whether prooxidants enhance HMGB1-induced TLR4 signaling through NF-κB activation. We used LPS-EK as a specific agonist for TLR4, and PPC and SIN-1 as in situ sources for ROS. As model systems, we used HEK-Blue cells (stably transfected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Because we found that the effects of LPS could be attenuated by a CCR2 antagonist, we suspect that the maintenance of hypersensitivity induced by LPS is mediated through activation of TLR4 and subsequent upregulation of MCP-1/CCL2. This finding was intriguing because activation of TLR4 elicits the generation of ROS/RNS in macrophages (Qin et al, 2005a, Zhang et al, 2015), yet in neurons TLR4 activation cannot maintain sensitivity without activation of the CCR2. Therefore, we propose that the quantitative, spatial and temporal aspects of ROS/RNS generation are critical for inducing DNA damage and will be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Because we found that the effects of LPS could be attenuated by a CCR2 antagonist, we suspect that the maintenance of hypersensitivity induced by LPS is mediated through activation of TLR4 and subsequent upregulation of MCP-1/CCL2. This finding was intriguing because activation of TLR4 elicits the generation of ROS/RNS in macrophages (Qin et al, 2005a, Zhang et al, 2015), yet in neurons TLR4 activation cannot maintain sensitivity without activation of the CCR2. Therefore, we propose that the quantitative, spatial and temporal aspects of ROS/RNS generation are critical for inducing DNA damage and will be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that these two stimulants can stimulate cells from both ends of the signaling pathway ( Figure 3) to induce changes in the nodes of the pathway. Based on these results 15,16 and previous reports, 17,18 the investigators speculated that the overexpression of HBx could inhibit the activity of NF-κB in normal hepatocytes, and NF-κB, HMGB1 and ROS were mutually regulated, TLR4 is also involved in regulation. Therefore, the investigators conclude that HBx suppresses the expression of HMGB1 and the production of ROS through NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 62%
“…In fact, only the disulfide (oxidized) isoform of this molecule activates TLR4 and promotes seizures but not the reduced form, which has instead chemoattractive properties [35,36]. …”
Section: The Il-1 Receptor (Il-1r1) and Toll-like Receptor (Tlr) Signmentioning
confidence: 99%